Information Context: Nature, Impact, and Role 5th International Conference on Conceptions of Library and Information Sciences, CoLIS 2005, Glasgow, UK, June 4-8, 2005 Proceedings - Crestani, Fabio.; Crestani, Fabio.; Ruthven, Ian.; Ruthven, Ian. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2005)
CoLIS 5 was the ?fth in the series of international conferences whose general aim is to provide a broad forum for critically exploring and analyzing research inareassuchascomputerscience,informationscienceandlibraryscience.CoLIS examinesthehistorical,theoretical,empiricalandtechnicalissuesrelatingtoour understanding and use of information, promoting an interdisciplinary approach to research. CoLIS seeks to provide a broad platform for the examination of context as it relates to our theoretical, empirical and technical development of information-centered disciplines. The theme for CoLIS 5 was the nature, impact and role of context within information-centered research. Context is a complex, dynamic and multi- - mensional concept that in?uences both humans and machines: how they behave individually and how they interact with each other. In CoLIS 5 we took an interdisciplinary approach to the issue of context to help us understand and the theoretical approaches to modelling and understanding context, incorporate contextual reasoning within technology, and develop a shared framework for promoting the exploration of context.